Identification of genes for reverse transcriptase-like enzymes in two Drosophila retrotransposons, 412 and gypsy; a rapid detection method of reverse transcriptase genes using YXDD box probes. - Yuki, S (1986)
Using synthetic oligonucleotides corresponding to the amino acid sequences best conserved among retroviral reverse transcriptases, we developed a rapid method to detect cloned DNA fragments with the genes for reverse transcriptases. By this technique followed by nucleotide sequence determination, nucleotide sequences coding for reverse transcriptase-like enzymes were identified in two Drosophila retrotransposons, gypsy and 412. Our sequence analysis suggested that there are at least two major groups of retrotransposons in Drosophila with respect to putative reverse transcriptases and both gypsy and 412 belong to a category of retrotransposons which have putative reverse transcriptases very similar in amino acid sequence to the counterpart of Moloney murine leukaemia virus, a typical mammalian retrovirus.